A Method of Shoulder Spica Cast Application In Shoulder Muscle Transfer Patients In Supine Position - Shah, Harsh R.; Bhandari, Praweshi Singh; Goklani, Mayur; Thatte, Mukund R (Indian Journal of Plastic Surgery, 2020)
Background Children with birth brachial plexus injury (BBPI) often require secondary surgery for the shoulder. The shoulder spica is necessary after shoulder muscle transfer surgery in babies with BBPI. However, its application can be difficult in the supine position under anesthesia. The authors describe a simple and cost-effective method of applying the shoulder spica cast without changing the supine position under anesthesia.Technique  While still under anesthesia, the child is placed in a supine position and then elevated on the wooden bar. The POP roll is wrapped around in a cylindrical manner, starting from the level one inch above the anterior superior iliac spine. The contralateral shoulder is also incorporated into the cast.Conclusion The spica application technique described comprises commonly available materials, such as a wooden plank, pair of bolsters, plaster of Paris rolls, and dressing materials overcoming the need for customized apparatus or the operation table. The materials are easy to assemble and thereby applicable just about anywhere. The task also becomes less challenging for the anesthetic in the supine position. This technique is easily reproducible and cost-effective.
Keywords: birth brachial plexus palsy; shoulder muscle transfer; shoulder spica cast